Jia-ga-song-tang protection against alcoholic liver and intestinal damage - Fang, Jiamin; Wu, Yuhuan; Gan, Changlian; Ruan, Shufang; He, Xiaoliang; Wang, Bixia; Wang, Ying; Yu, Jingtao; Sang, Chuanlan; Zeren, Dawa; Xiong, Tianqin (Frontiers in Pharmacology, 2022)
Gut-liver axis and cellular homeostasis play key roles in alcohol liver disease (ALD). Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a stress-sensitive guarantor of cellular homeostasis. We investigated whether the beneficial effects and underlying mechanisms of Jia-ga-song Tang (JGST) against ALD were associated with gut-liver axis and cellular homeostasis. A predictive network depicting the relationship between Jia-Ga-Song-Tang(JGST) and alcoholic liver disease (ALD) was designed by Network pharmacology. Next, 5% v/v Lieber-DeCarli alcohol liquid diet was used to establish the ALD. JGST protected the liver damage, repaired the intestines to alleviate the Two-hit on the liver, and balanced the cellular homeostasis. It was manifested in repairing the liver and intestinal pathological structure, reducing serum ALT, AST, and liver TG, TC, MDA, CAT, and increasing liver GSH, and intestine GSH-Px. JGST mainly inhibited the liver mRNA levels of HO-1, NQO1, GCLC, FASN, and PPARα and activated the intestinal mRNA levels of HO-1 and NQO1, while inhibiting the liver protein levels of HO-1, NQO1. Furthermore, LPS and LBP in the plasma and the expression of inflammatory factors such as IL-1β, TNF-α, IL-6, TGFβ1, CD14, and Myd88 were reduced after treatment to prove that JGST protects the liver from Two-hit. Ethanol was used to intervene in HepG2 and IEC-6 to establish an ALD cell model and treated by Germacrone, ML385, and TBHQ. repaired the intestinal barrier, and inhibited Nrf2 in IEC-6, but protect the HepG2 by activating Nrf2 to balance cellular homeostasis. Our results reinforce that JGST provides an effective protective method for alcoholic liver disease (ALD) by regulating Gut-liver axis and cellular homeostasis.